Cultural Conceptions of Mental Health and Therapy - Marsella, Anthony J. author. aut Link
XII, 414 p.
Keywords: Within the past two decades, there has been an increased interest in the study of culture and mental health relationships. This interest has extended across many academic and professional disciplines, including anthropology, psychology, sociology, psychiatry, public health and social work, and has resulted in many books and scientific papers emphasizing the role of sociocultural factors in the etiology, epidemiology, manifestation and treatment of mental disorders. It is now evident that sociocultural variables are inextricably linked to all aspects of both normal and abnormal human behavior. But, in spite of the massive accumulation of data regarding culture and mental health relationships, sociocultural factors have still not been incorporated into existing biological and psychological perspectives on mental disorder and therapy. Psychiatry, the Western medical specialty concerned with mental disorders, has for the most part continued to ignore socio-cultural factors in its theoretical and applied approaches to the problem. The major reason for this is psychiatry's continued commitment to a disease conception of mental disorder which assumes that mental disorders are largely biologically-caused illnesses which are universally represented in etiology and manifestation. Within this perspective, mental disorders are regarded as caused by universal processes which lead to discrete and recognizable symptoms regardless of the culture in which they occur. However, this perspective is now the subject of growing criticism and debate.